2010
DOI: 10.1111/j.1462-2920.2009.02150.x
|View full text |Cite
|
Sign up to set email alerts
|

Chloroform respiration to dichloromethane by a Dehalobacter population

Abstract: Chloroform (CF), or trichloromethane, is an ubiquitous environmental pollutant because of its widespread industrial use, historically poor disposal and recalcitrance to biodegradation. Chloroform is a potent inhibitor of metabolism and no known organism uses it as a growth substrate. We discovered that CF was rapidly and sustainably dechlorinated in the course of investigating anaerobic reductive dechlorination of 1,1,1-trichloroethane in a Dehalobacter-containing culture. Like 1,1,1-trichloroethane dechlorina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
116
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(130 citation statements)
references
References 29 publications
7
116
0
2
Order By: Relevance
“…CF can be cometabolically transformed under sulfate-reducing and methanogenic conditions (11,30), and a recent report demonstrated growth of a Dehalobacter sp. linked to reductive dechlorination of CF to DCM and inorganic chloride as end products (8). This finding suggested that CF organohalide respiration provides an additional source of DCM in anoxic environments.…”
mentioning
confidence: 71%
See 1 more Smart Citation
“…CF can be cometabolically transformed under sulfate-reducing and methanogenic conditions (11,30), and a recent report demonstrated growth of a Dehalobacter sp. linked to reductive dechlorination of CF to DCM and inorganic chloride as end products (8). This finding suggested that CF organohalide respiration provides an additional source of DCM in anoxic environments.…”
mentioning
confidence: 71%
“…Dehalobacter spp. respire chlorinated ethenes (14), chlorinated ethanes (9, 27), 4,5,6,7-tetrachlorophthalide (31), ␤-hexachlorocyclohexane (28), and CF (8) and recently have been implicated in reductive dechlorination of dichlorobenzenes and monochlorobenzene (24).…”
mentioning
confidence: 99%
“…[11][12][13][14], suggesting that the degradation potential of the genus Dehalobacter is largely beyond PCE and TCE. Finally, fermentation of dichloromethane by members of Dehalobacter has been shown [15,16], suggesting that not necessarily all members of this genus are obligate OHR bacteria (OHRB).…”
Section: Introductionmentioning
confidence: 99%
“…Much fundamental interest is directed at the underlying reaction chemistry of the C-Cl bond [2][3][4]. The widespread industrial application of chlorinated hydrocarbons as solvents, chemical intermediates and pesticides resulted in environmental contamination, with adverse effects on drinking water quality and ecosystem and human health [5][6][7]. A specific focus has therefore been on their reductive dehalogenation to non-halogenated hydrocarbons, where detoxification is achieved by reductive cleavage of the carbon-chlorine bonds.…”
Section: Introductionmentioning
confidence: 99%